2020
DOI: 10.7150/jca.41783
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Curcumin and 5-Fluorouracil on the Hepatocellular Carcinoma In vivo and vitro through regulating the expression of COX-2 and NF-κB

et al.

Abstract: Curcumin (CU) has shown broad anti-cancer effects. 5-fluorouracil (5-FU) has been a conventional chemotherapeutic agent for hepatocellular carcinoma. Unfortunately, the nonspecific cytotoxicity and multidrug resistance caused by long-term use limited the clinical efficacy of 5-FU. This study was aimed to investigate whether the combination of CU and 5-FU could generate synergistic effect in inhibiting the human hepatocellular carcinoma. The results of cytotoxicity test showed that compared with applying single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…Numerous studies have reported that the extracts of Chinese traditional medicines, such as curcumin, gypenosides, quercetin and oxymatrine could act as chemosensitizer to enhance the efficacy of 5-Fu in HCC cells [26,[30][31][32]. However, whether CP-25 can become a good chemosensitizer to amplify the effectiveness of chemotherapy in clinic is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported that the extracts of Chinese traditional medicines, such as curcumin, gypenosides, quercetin and oxymatrine could act as chemosensitizer to enhance the efficacy of 5-Fu in HCC cells [26,[30][31][32]. However, whether CP-25 can become a good chemosensitizer to amplify the effectiveness of chemotherapy in clinic is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…And then the test was divided into four groups including: control, CP-25 alone (10 -5 mol/L), 5-Fu alone (25 μg/ml), 25 μg/ml 5-Fu +10 -5 mol/L CP-25. The apoptosis rate was detected by flow cytometry and the invasion and metastasis ability of HepG2 and Bel-7402 were observed by scratch test and transwell [26]. The expression of P53, Caspase-9, Cytochrome-C, Bax, Bcl-2 in HepG2 and Bel-7402, and MMP-2 and MMP-9 in Bel-7402 were assayed by western blot (reference 2.6).…”
Section: Examination Of the Effects Of Combination Agents On Cellsmentioning
confidence: 99%
“…However, the drug resistance and high toxicity limited the efficacy of 5-FU (Gao, Yu et al 2018). Therefore, it is necessary to find more effective chemotherapeutic drugs and/or combination therapy for HCC (Xu, Guo et al 2020). MSCs are a group of adult stem cells which can migrate to tissue injury sites and tumor sites.…”
Section: Discussionmentioning
confidence: 99%
“…Xenograft model of hepatocellular carcinoma H22 cells in nude male mice, showed better inhibition of tumor growth on daily dose of 100 mg/kg curcumin through intragastric administration for 2 weeks as compared to control group [ 153 ] . The subcutaneous tumor xenograft of human hepatocellular carcinoma SMMC-7721 cells in BALB/c nude female mice showed minimum tumor volume and highest tumor inhibitory rate (TIR) of 70% on combinatorial treatment of curcumin (56.65 mg/kg) + 5-FU (10 mg/kg) as compared to the control [ 154 ] . Human hepatocellular carcinoma HepG2 cells xenograft tumor in female BALB/c nude mice showed more than 50% reduction in tumor volume on daily intraperitoneal administration of curcumin (200 mg/kg) for one month with indications of autophagy [ 155 ] .…”
Section: Curcumin: Inroads Into In Vivomentioning
confidence: 99%